2005
DOI: 10.1002/ptr.1690
|View full text |Cite
|
Sign up to set email alerts
|

Histological investigations on the effects of feeding a diet containing red hot pepper on the reproductive organs of the chicken

Abstract: In the present study the growth and reproductive organ differences in chickens fed a diet containing 1% red hot pepper (10 g/kg diet) from the first day of age were investigated. In birds fed with the experimental diet it was observed that the abdominal fat content decreased. During the experiment the increase in weight gain in the treated group in the first 4 months was reversed in favour of the control group in month 5. Follicular development in the treated group was faster and laying started 11 days before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Efficient chili pepper active compounds are capsaicin, capsisin and capsantine. Chili pepper fruits are used by broiler and layer producers for increasing chicken appetite (Ozer et al, 2005), darkening the yolk color and improving laying performance (Ozer et al, 2006). Al-Kassie et al (2012) indicated that dietary inclusion of hot red pepper decreased the heterophil/lymphocytes (H/L) ratio, indicating its role in the immune system of birds.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient chili pepper active compounds are capsaicin, capsisin and capsantine. Chili pepper fruits are used by broiler and layer producers for increasing chicken appetite (Ozer et al, 2005), darkening the yolk color and improving laying performance (Ozer et al, 2006). Al-Kassie et al (2012) indicated that dietary inclusion of hot red pepper decreased the heterophil/lymphocytes (H/L) ratio, indicating its role in the immune system of birds.…”
Section: Introductionmentioning
confidence: 99%
“…Red pepper fruits ( Capsicum annuum L.) are commonly eaten as vegetables and are an important source of spice (Özer et al., 2005). They are a good source of vitamins C and E (Palevitch and Craker, 1995; Daood et al., 1996), as well as provitamin A and carotenoid compounds, with well‐known antioxidant properties (Krinsky, 1994, 2001; Matsufuji et al., 1998).…”
Section: Introductionmentioning
confidence: 99%
“…(1986a,b) have reported that capsaicin enhanced the energy metabolism of rats through its beta‐adrenergic action and decreased perirenal adipose tissue weight. In chickens, 1% dietary red pepper caused faster development of ovaries (Özer et al., 2005), and capsaicin significantly increased intestinal mucus production (Jamroz et al., 2006). The small intestine is one of the most important sites of nutrient absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Physiologically, foods such as those containing capsaicin have been found to influence metabolism or homeostasis, sometimes resulting in clinically important effects on animal gastrointestinal, cardiovascular and respiratory systems [7,19]. Human studies have demonstrated that red pepper consumption decreases appetite while it increases satiety [26], as well as energy expenditure [28], which is thought to be mediated by increased activity of sympathetic nervous system by capsaicin [25].…”
Section: Introductionmentioning
confidence: 99%